BMI, body mass and height, and the level of sports competence in the participants of the Winter Olympic Games in 2010 - Szmatlan Gabrys, U.; Stanula, A.; Ozimek, M. U. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Somatic parameters such as body height, body weight or body mass index (BMI) have a bearing on training strategy, as they can affect the technique and tactics of competition and athlete`s specialization within a given discipline (Wilmore, 1983). The aim of this study was establish the body height, body mass, and BMI values characterizing the athletes that participated in the Winter Olympic Games in 2010 in Vancouver, and to assess whether these are associated with the metabolic requirements of their respective sports. Methods: The sample consisted of athletes in the top 20 places of each of 14 sports disciplines played at the WOG in 2010 (1460 cases). The sampled athletes were grouped according to the predominant type of energy metabolism during competition using criteria such as duration and intensity of effort (Åstrand et al., 2003). A cluster analysis was then applied to aggregate the particular disciplines and events of the Winter Olympic Games into groups based on anthropometric characteristics. Results: The groups of winter sports derived from a cluster analysis based on the somatic parameters and those produced based on the predominant type of energy metabolism were dissimilar. This implies that in particular disciplines of most winter sports (excluding luge, bobsleigh and alpine skiing) the athletes have different body build, so a single profile of the athlete cannot be established. Discussion: The contemporary winter athlete has welltrained strength and anaerobic endurance. These characteristics are related to larger body mass and higher BMI values. Strength and speed endurance training is becoming increasingly important for athletes` performance. The results seem to indicate that the somatic parameters of the athletes in winter sports disciplines such as cross country, biathlon, and speed skating reflect a shift in the direction of athletic training (Stanula et al., 2013).